Development of aromatic polyamide membranes for pervaporation and vapor permeation - Teng, M-Y; Lee, K-R; Fan, S-C; Liaw, D-J; Huang, J.; Lai, J-Y
The pervaporation and vapor permeation performances of a series of fluorine-containing aromatic polyamide membranes for various alcohol mixtures were investigated. Compared with pervaporation, vapor permeation effectively increases the permselectivity of water. The solubility of alcohol in an aromatic membrane is higher than that of water, but the diffusivity of water across the membrane is higher than that of the alcohols. In addition, the relationship between the polymer structure and pervaporation performance was obtained. It was found that the permeation rate can be increased by the introduction of bulky substituted groups and arylene ether groups into the polymer backbone.
Keywords: PERVAPORATION; VAPOR PERMEATION; FLUORINE-CONTAINING AROMATIC POLYAMIDE; MEMBRANE